1987
DOI: 10.1104/pp.83.3.475
|View full text |Cite
|
Sign up to set email alerts
|

Enzymic Synthesis of Caffeoylglucaric Acid from Chlorogenic Acid and Glucaric Acid by a Protein Preparation from Tomato Cotyledons

Abstract: The phenylpropane metabolism of tomato (Lycopersicon escukntm Mill) cotyledons was investigated. The (10,18) and glucaric acid (3). To date two mechanisms for the formation of such esters have been described (1); one involving the hydroxycinnamoyl-CoA thioester and the other one the l-O-(hydroxycinnamic acid)-acyl glucoside. The former mechanism was first shown to operate in the formation of chlorogenic acid (12), the 5-0-caffeoylquinic acid (6), in Nicotiana cell-suspension cultures and the latter one in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 13 publications
1
32
0
1
Order By: Relevance
“…1B). The structures of known compounds were determined by comparing their spectroscopic and/or chromatographic data with values in the literature and were identified as 3-O-[(trans)-caffeoyl]-glucaric acid (A) (Maas et al, 2009;Nagels et al, 1982), 2-O-[(trans)-caffeoyl]-glucaric acid (B-1) (Strack et al, 1987), 5-O-[(trans)-caffeoyl]-quinic acid (neo-chlorogenic acid)…”
Section: Discussionmentioning
confidence: 99%
“…1B). The structures of known compounds were determined by comparing their spectroscopic and/or chromatographic data with values in the literature and were identified as 3-O-[(trans)-caffeoyl]-glucaric acid (A) (Maas et al, 2009;Nagels et al, 1982), 2-O-[(trans)-caffeoyl]-glucaric acid (B-1) (Strack et al, 1987), 5-O-[(trans)-caffeoyl]-quinic acid (neo-chlorogenic acid)…”
Section: Discussionmentioning
confidence: 99%
“…26,27 The concentration of chlorogenic acid oligomers are known to decrease along ripeness, which reflects in the better quality of the beverage obtained with ripe cherry beans. The variability of lipids concentration was studied by Jham et al, 28 who showed a pronounced decrease of diacylglycerols in coffees beans from unripe to ripe, the same happening with fatty acids.…”
Section: Ripenessmentioning
confidence: 99%
“…For any organ where a metabolite was absent or excluded in more than 15 out of the total of 45 Strack et al (1987) b Moco et al (2006) c Iijima et al (2008) d Vallverdu-Queralt et al (2010) e Tikunov et al (2010) f Gómez-Romero et al (2010) g Ferreres et al (2010) h Butelli et al (2008) i Bovy et al (2002) j Schmidt et al (2011) samples, this metabolite was removed from the mixed model analysis. The number of metabolites analysed for each organ is indicated in Supplementary Table S4.…”
Section: Metabolite Identification Using High Mass Resolution Fragmenmentioning
confidence: 99%
“…In addition, compounds described in the literature to be present in WT tomato fruits (Gómez-Romero et al 2010;Tikunov et al 2010;Vallverdu-Queralt et al 2010), transgenic tomato fruits (Butelli et al 2008), transgenic tomato seedlings (Bovy et al 2002), tomato seeds (Ferreres et al 2010) and tomato leaves (Strack et al 1987;Lawson et al 1997;Schmidt et al 2011) were incorporated into the list of known tomato compounds. New metabolites were putatively annotated based on their elemental formulae calculated from the observed accurate mass and using additional information such as UV absorption spectra and high-mass resolution fragmentation data.…”
Section: Metabolite Annotationmentioning
confidence: 99%